Jubileusz 75-lecia Poznańskiego Wydziału Prawa - Borkowska - Bagieńska, Ewa; Błażejczak, Bogdan; Łączkowski, Wojciech; Ziembiński, Zygmunt; Janowicz, Zbigniew; Olszewski, Henryk (Wydział Prawa i Administracji UAM, 1994)
This set of papers comprises the speech, made by the Professor Ewa Borkowska Bagieńska, Dean of the Faculty of Law and Administration, Adam Mickiewicz University in Poznań, on the occasion of the jubilee, in which she outlined the origin, history and contemporary development of the Faculty. It also includes articles devoted to the merits of five deceased Professors who may be considered the most eminent personalities of the Faculty of Law and Administration. They were: Prof. Zygmunt Wojciechowski, historian, specialist in the history of the Polish State and Law, co-creator of Poznań Historic School, founder of the Western Institute and a great politician, Professor Edward Taylor, an outstanding economist, teacher of many scholars, Professor Czesław Znamierowski, philosopher, theoretician, specialist in the law, sociologist and moralist, Professor Marian Zimmermann, linking with the heritage of the European science of administrative law, and Professor Alfred Ohanowicz, eminent specialist in civil law, editor-in-chief and later honourary editor of the Ruch Prawniczy, Ekonomiczny i Socjologiczny published by the Faculty.
75-years of Poznań Faculty of Law